2018
DOI: 10.1111/hsc.12674
|View full text |Cite
|
Sign up to set email alerts
|

The association between social cohesion and community disaster resilience: A cross‐sectional study

Abstract: A cross‐sectional study design was created, using the Index of Perceived Community Resilience (IPCR) and Buckner's Index of Cohesion (BIC) to survey 386 flood evacuees from six communities in Kelantan, Malaysia, in 2015. The respondents were mostly female (54.7%); lived in basic housing (95.6%); average income (55.9%); secondary level schooling (81.1%); not involved with community organisations (95.1%), volunteering activities (91.2%), or emergency teams (96.9%); inexperience with injury during flooding (94%);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 26 publications
0
39
1
Order By: Relevance
“…Many emphasize the importance of stakeholder engagement in this area of work and research. 1,14,18,19,28,29,[36][37][38][39][40]42 This body of literature has many common themes that agree on factors that promote social cohesion in disaster recovery. They include (a) government interventions (financial stimulus, social protections, etc), (b) government protocols for communicating with the public and stakeholder engagement, (c) community-led and localized recovery efforts, and (d) community-building events and opportunities.…”
Section: Social Cohesion: State Of the Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Many emphasize the importance of stakeholder engagement in this area of work and research. 1,14,18,19,28,29,[36][37][38][39][40]42 This body of literature has many common themes that agree on factors that promote social cohesion in disaster recovery. They include (a) government interventions (financial stimulus, social protections, etc), (b) government protocols for communicating with the public and stakeholder engagement, (c) community-led and localized recovery efforts, and (d) community-building events and opportunities.…”
Section: Social Cohesion: State Of the Sciencementioning
confidence: 99%
“…Social cohesion refers to the degree of social connectedness and solidarity between different community groups within a society, as well as the level of trust and connectedness between individuals and across community groups. [1][2][3] It exists on multiple levels of organization, from the household level through international relations, all of which are intertwined and interact with one another. 4 The relationships among individuals and communities and their local, regional, and national levels of government are affected by social cohesion.…”
Section: Social Cohesion and Disaster Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies show that higher levels of community cohesion are associated with a lower risk of individual violent victimization and crime rates (Hirschfield & Bowers, 1997;Lee, 2000;Olutola & Bello, 2016). In addition, a number of studies demonstrated the significant link between the community cohesion and resilience (Ludin, Rohaizat, & Arbon, 2019;Patel & Gleason, 2018). Community resilience refers to the capacity of a community to survive, respond to, and recover from adverse events and community cohesion plays a key role in this process.…”
Section: Community Policingmentioning
confidence: 99%
“…Kim, et al explore climate justice and flood risk with specific reference to community resilience at the county-level, results suggest that community social and ecological characteristics were influenced by flood losses and that social capital and local proactive planning and policy measures lead to lower disaster losses and enhanced community resilience [30]. Ludin, et al made use of the Index of Perceived Community Resilience (IPCR) and Buckner’s Index of Cohesion (BIC) to survey 386 flood evacuees from six communities in Kelantan, Malaysia, and their results showed that the higher social cohesion and social resilience, the higher disaster resilience [31].…”
Section: Literature Reviewmentioning
confidence: 99%